The Triple Burden of Malnutrition Among Adolescents in Indonesia. Issue 1 (June 2021) - Rah, Jee Hyun; Melse-Boonstra, Alida; Agustina, Rina; van Zutphen, Kesso Gabrielle; Kraemer, Klaus
Background: Indonesia is a prime example of the triple burden of malnutrition. Indonesian adolescents are among the hardest hit, with approximately one in four adolescent girls suffering from anemia, while nearly one in seven adolescents is overweight or obese. Objectives: The present editorial provides a snapshot of the various research papers included in this Supplement, which calls for increased attention to adolescent nutrition in Indonesia and beyond. Results: Despite major steps to reduce undernutrition and overweight, including a renewed focus on anemia among adolescent girls, major gaps remain in our understanding of various nutrition issues concerning adolescents. These include various drivers and determinants of the triple burden of malnutrition, evidence-based interventions that are supported by large-scale implementation research and evaluation, and effective delivery platforms to reach the most vulnerable groups of adolescents. Conclusion: The time has come to position adolescent nutrition as central to development, and mainstream it into health sector plans, strategies, and policies. It is our hope that this issue will stimulate the urgently needed interventions, implementation research and required programs that will safeguard the nutritional wellbeing of today's forgotten generation.